Recent Themes in the Philosophy of Science
XXIV, 216 p.
Keywords: Australia and New Zealand boast an active community of scholars working in the field of history, philosophy and social studies of science. Australasian Studies in History and Philosophy of Science aims to provide a distinctive publication outlet for their work. Each volume comprises a group of thematically-connected essays edited by scholars based in Australia or New Zealand with special expertise in that particular area. In each volume, a majority ofthe contributors are from Australia or New Zealand. Contributions from elsewhere are by no means ruled out, however, and are actively encouraged wherever appropriate to the balance of the volume in question. Earlier volumes in the series have been welcomed for significantly advancing the discussion of the topics they have dealt with. I believe that the present volume will be greeted equally enthusiastically by readers in many parts of the world. R. W. Home General Editor Australasian Studies in History And Philosophy of Science viii ACKNOWLEDGEMENTS The majority of the papers in this collection had their origin in the 2001 Australasian Association for History, Philosophy, and Social Studies of Science annual conference, held at the University of Melbourne, where streams of papers on the themes of scientific realism and commonsense were organised.